Some factors affecting the production of second generation ethanol from eucalyptus, sugarcane bagasse and sugarcane straw - Carvalho, Danila Morais de (2016)
The ethanol has been considered a promising biofuel to replace fossil-based fuels. The strategic use of eucalyptus, sugarcane bagasse and sugarcane straw in second generation technology to ethanol production was investigated in this work, by performing various pretreatment processes followed by simultaneous saccharification and fermentation (SSF). In article I it is presented the chemical characterization of eucalyptus, sugarcane bagasse and straw before and after hydrothermal (H 2 O), diluted acid (4.5% H 2 SO 4 ) and alkaline (15% NaOH) pretreatments. It was determined that the significant amount of silica present in sugarcane bagasse and straw led to overestimation of Klason lignin of these biomasses. A novel approach to report the chemical composition of biomasses, based on the complete mass balance, was suggested and proved to be useful to assess both, raw materials and pretreated biomasses. The formation of pseudo-extractives in eucalyptus wood and pseudo-lignin in bagasse and straw as result of pretreatments was observed. Article II presents the chemical and structural characterization of xylans isolated from eucalyptus, bagasse and straw via two different methods, namely: peracetic acid delignification followed by dimethyl sulfoxide extraction and sodium chlorite delignification followed by dimethyl sulfoxide extraction. The xylan obtained from eucalyptus was identified as an O-acetyl-4-O-methylglucuronoxylan type, containing 39 acetyl groups units and 11 4-O-methylglucuronic acids per 100 units of xylose on the backbone. In addition, one 4-O-methylglucuronic acid was also substituted by one terminal galactosyl unit. The xylan obtained from bagasse and straw was an arabinoxylan type, which contained 100 xylose units: 29 acetyl groups units: 5 arabinofuranosyl units for bagasse, proporcionally, and 100 xylose units: 8 acetyl groups units: 6 arabinofuranosyl units for straw, proporcionally. Article III describes the effect of hydrothermal and diluted acid (1.5, 3.0 and 4.5% H 2 SO 4 ) pretreatments on the chemical composition of biomasses and their subsequent conversion into ethanol. It was observed that lowering pretreatment pH resulted in improved lignin and carbohydrates removal. The eucalyptus presented the highest ethanol production after hydrothermal pretreatment, but with relative low yield. After acid pretreatments, bagasse and straw showed higher ethanol productions then eucalyptus. The pretreatment performed at 4.5% H 2 SO 4 was the most efficient. Article IV assesses the effect of alkaline charge during alkaline (5, 10 and 15% NaOH) pretreatments on the chemical composition of biomasses and their subsequent conversion into ethanol. It was observed that higher alkaline charge provided the highest lignin and carbohydrates removal. For the alkaline pretreatments, the bagasse proved to be the most promising biomass for ethanol production. The pretreatment with 15% NaOH was the most efficient. Article V presents an optimization of the cold alkaline extraction (CAE) pretreatment regarding temperature (20oC, 30oC and 40oC), reaction time (10, 35 and 60 min) and NaOH concentration (70, 90 and 110 g L -1 ), focusing on xylan removal from biomasses and subsequent conversion of the xylan-depleted biomasses into ethanol. The optimal conditions for xylan removal from eucalyptus wood, sugarcane bagasse and sugarcane straw were, respectively: 40oC, 60 min and 70 g L -1 NaOH; 33oC, 60 min and 110 g L -1 NaOH; and 31oC, 55 min and 110 g L -1 NaOH. Under these pretreatments conditions, substantial amounts of lignin were also removed from the biomasses. For the eucalyptus wood, the formation of pseudo-extractives was observed during the CAE pretreatments. The sugarcane straw pretreated with CAE was the most promising biomass for production of second generation ethanol. For the CAE pretreatments, higher ethanol yields were achieved with sugarcane bagasse and straw in relation to eucalyptus wood. In summary, the results accumulated from this doctoral thesis suggested that bagasse and straw are suitable biomasses for production of second generation ethanol. The use of these lignocellulosic biomasses creates the possibility of integrating first and second platforms for ethanol production, which turns residues into main product.